2004
DOI: 10.1016/j.bone.2004.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Fetal bone cells for tissue engineering

Abstract: We envision the use of human fetal bone cells for engineered regeneration of adult skeletal tissue. A description of their cellular function is then necessary. To our knowledge, there is no description of human primary fetal bone cells treated with differentiation factors. The characterization of fetal bone cells is particularly important as the pattern of secreted proteins from osteoblasts has been shown to change during aging. In the first part of this work, human primary fetal bone cells were compared to ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
75
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 72 publications
5
75
0
Order By: Relevance
“…Scaffolds developed in this study showed high osteoconductive potential, allowing proliferation of bone cells through the porous structures. Fetal bone cells were already characterized for their high osteogenic potential, 27 and their proliferative aptitude observed on artificial structures is of major interest from the perspective of the use of human primary fetal bone cells in tissue engineering. During the exposure, fetal and adult bone cells seeded on the scaffolds were pushed toward differentiation, and osteoblastic genes such as cbfa-1, ␣ 1 chain of type I collagen, alkaline phosphatase, and osteocalcin were expressed (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scaffolds developed in this study showed high osteoconductive potential, allowing proliferation of bone cells through the porous structures. Fetal bone cells were already characterized for their high osteogenic potential, 27 and their proliferative aptitude observed on artificial structures is of major interest from the perspective of the use of human primary fetal bone cells in tissue engineering. During the exposure, fetal and adult bone cells seeded on the scaffolds were pushed toward differentiation, and osteoblastic genes such as cbfa-1, ␣ 1 chain of type I collagen, alkaline phosphatase, and osteocalcin were expressed (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…26 The interesting potential of fetal bone cells for tissue engineering was demonstrated on the basis of their rapid growth rate and their responsiveness to differentiation factors. 27 In this study, fetal and adult bone cells were each seeded on the same batches of scaffolds to compare their interactions. We demonstrate here for the first time that once seeded with human fetal bone cells, PLA/ceramic composite osteoconductive scaffoldsprocessed by supercritical gas foaming-give a promising approach in tissue engineering due to the high osteogenic potential of these cells.…”
Section: Introduction Bmentioning
confidence: 99%
“…The accepted paradigm in bone tissue engineering is to combine a scaffold with cells and/or growth factors [1][2][3][4][5][6]. The scaffold is used for its osteoconductive properties [7,8] and the cells or growth factors are used for their osteoinductive or osteogenic properties [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Fetal bone cells were shown to proliferate, differentiate and finally to mineralize their extra cellular matrix in vitro [1]. For these reasons, we decided to test their association with porous scaffolds for bone repair in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, fetal bone cells were characterized in vitro to investigate their potential use for tissue engineering [1]. They were shown to be able to proliferate and differentiate into mature osteoblasts in vitro when seeded on PLA/TCP scaffolds [2].…”
Section: Introductionmentioning
confidence: 99%